Therapeutic Potentials of Some Selected Medicinal Plant Extracts against Helicobacter pylori Infection: In Vivo Activities and Implications - Egbe, P. A.; Umeaku, C. N.; Iheukwumere, I. H.; Iheukwumere, C. M.; Onwuasoanya, U. F.; Ezenwata, I. S.; Afulukwe, S. C.; Ike, V. E.; Ezeumeh, E. N. (IPS Journal of Applied Microbiology and Biotechnology, 2025)
Helicobacter pylori infection is the major cause of gastrointestinal diseases worldwide, and the high resistance of different strains against antibiotics has necessitated the search for alternative agents. Medicinal plants have shown promising results in treating various ailments, but their in vivo efficacy against H. pylori infection requires further investigation. The study focused on the in vivo activity of some selected mixtures of medicinal plants against H. pylori infection. A total of 186 stool and blood samples were collected and screened for HP using Columbia agar supplemented with minor nutrients. The isolates were characterized using their morphological, biochemical and molecular properties. The phytochemical constituents of Zingiber officinale (ZO) rhizome, Hunteria umbellate (HU) leaves and Neubouda laevis (NL) leaf extracts were determined using gravimetric and spectrophotometric methods. The therapeutic potential of the extracts was carried out using in vivo method. Analysis of variance (ANOVA) and student “t” test were used to analyze the data generated from the study at 95 % confidence level. H. pylori strain K154 (HPK154), H. pylori strain BS07 (HPBS07), H. pylori strain K93 (HPK93) and H. pylori strain K115 (HPK115) were mostly encountered in the study. Alkaloids, saponins, phenolics, flavonoids, tannins, and glycosides were the major phytochemicals significantly (P<0.05) detected in the plant extracts. The in vivo treatment using the extracts significantly (P<0.05) reduced the clinical manifestation of the pathogens, and HU+NL+ZO augmented with levofloxacin showed the highest healing activity. Therefore, the study has shown that ZO, HU and NL had significant therapeutic activities against strains of HP, and HU+NL+ZO augmented with levofloxacin was most effective.